2002
DOI: 10.1002/asi.10139
|View full text |Cite
|
Sign up to set email alerts
|

Rotation and scale invariant wavelet feature for content‐based texture image retrieval

Abstract: This article introduces an effective rotation and scale invariant log-polar wavelet texture feature for image retrieval. The proposed feature is an attempt to enhance the existing content-based image retrieval systems that largely present difficulty in coping with images with changes in orientations and scales. The underlying feature extraction process involves a log-polar transform followed by an adaptive row shift invariant wavelet packet transform. The log-polar transform converts a given image into a rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Texture features. Many texture features have been investigated in the past, including the conventional pyramid-structured wavelet transform (PWT) features, tree-structured wavelet transform (TWT) features, the multi-resolution simultaneous autoregressive model (MR-SAR) features and the Gabor wavelet features [18]. Experiments have been conducted and have found that the Gabor features produce the best performance [2,20].…”
Section: Content-based Image Retrievalmentioning
confidence: 99%
“…Texture features. Many texture features have been investigated in the past, including the conventional pyramid-structured wavelet transform (PWT) features, tree-structured wavelet transform (TWT) features, the multi-resolution simultaneous autoregressive model (MR-SAR) features and the Gabor wavelet features [18]. Experiments have been conducted and have found that the Gabor features produce the best performance [2,20].…”
Section: Content-based Image Retrievalmentioning
confidence: 99%
“…Some of the most recent solutions propose invariant features to geometric distortions [19] [20]. Once again, an effective retrieval method can be designed by using affine invariant interest points as features, without the need of performing a matching operation.…”
Section: Introductionmentioning
confidence: 99%